2001
DOI: 10.1002/ddr.1103
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the inhibitory action of ATP in rat hippocampus

Abstract: We have already shown, by calcium imaging with an electrophysiological method and direct detection of glutamate, that ATP inhibits the glutamate release from cultured rat hippocampus [Koizumi and Inoue, 1997;Inoue et al., 1999], although ATP induces fast synaptic currents and produces an increase in intracellular calcium in a subpopulation of cultured hippocampal neurons Inoue et al., 1995]. We have examined the mechanism of the inhibition by ATP using the FM1-43 method as well as the methods mentioned above.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…There is a body of evidence that provides a clear indication of a widespread role for P2Y receptors in rat cerebral neurons–a presynaptic role on nerve terminals. Accordingly, several reports have shown that release of biogenic amines (noradrenaline, dopamine and 5‐hydroxytryptamine) and glutamate is regulated by presynaptic P2Y receptors (von Kugelgen et al ., 1994; Koch et al ., 1995; 1997; Zhang et al ., 1995; Bennett & Boarder, 2000; Inoue & Koizumi, 2001). From the current studies there emerges evidence for a second role for P2Y receptors in rat brain: glial cells are apparently influenced by nucleotides via a phospholipase C‐coupled P2Y 1 receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a body of evidence that provides a clear indication of a widespread role for P2Y receptors in rat cerebral neurons–a presynaptic role on nerve terminals. Accordingly, several reports have shown that release of biogenic amines (noradrenaline, dopamine and 5‐hydroxytryptamine) and glutamate is regulated by presynaptic P2Y receptors (von Kugelgen et al ., 1994; Koch et al ., 1995; 1997; Zhang et al ., 1995; Bennett & Boarder, 2000; Inoue & Koizumi, 2001). From the current studies there emerges evidence for a second role for P2Y receptors in rat brain: glial cells are apparently influenced by nucleotides via a phospholipase C‐coupled P2Y 1 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Initially this related to presynaptic P2Y receptor regulation of release of the amines noradrenaline, 5‐hydroxytryptamine and dopamine (von Kugelgen et al ., 1994; Koch et al ., 1995; 1997; Krugel et al ., 2001a, 2001b). However, we and others have recently presented evidence that directly implicates P2Y receptors in the presynaptic regulation of glutamate release (Bennett & Boarder, 2000; Inoue & Koizumi, 2001). These investigations suggest a widespread influence of P2Y receptors on brain function.…”
Section: Introductionmentioning
confidence: 97%